Is Zika Virus an Emerging TORCH Agent? An Invited Commentary. Issue 1 (16th May 2017) - Mehrjardi, Mohammad Zare
Zika virus (ZIKV) is a mosquito-borne arbovirus from the family Flaviviridae, which had caused some epidemics since its discovery in 1947 without any significant impacts on public health. In 2015, however, a 20-fold increase in congenital microcephaly cases in northeastern Brazil was attributed to prenatally acquired ZIKV infection. Traditionally, TORCH agents have 4 common characteristics including causing a mild illness in infected mother, vertical transmission to fetus, developing several anomalies in the affected fetus, and in some instances, maternal therapy may not ameliorate fetal prognosis. Prenatal ZIKV infection has shown the aforementioned characteristics during the recent epidemics in South America and the Caribbean region; therefore, it should be considered as an emerging TORCH agent that may seriously threaten public health. Fetal ultrasound can be used as a safe, inexpensive, and easy-to-access imaging modality for detecting suspicious cases of congenital Zika syndrome in utero and suggesting confirmatory diagnostic examinations to these patients.